Clinical and Serological Predictors of Suicide in Schizophrenia and Major Mood Disorders. Issue 3 (March 2018) - Dickerson, Faith; Origoni, Andrea; Schweinfurth, Lucy A.B.; Stallings, Cassie; Savage, Christina L.G.; Sweeney, Kevin; Katsafanas, Emily; Wilcox, Holly C.; Khushalani, Sunil; Yolken, Robert
Abstract : Abstract: Persons with serious mental illness are at high risk for suicide, but this outcome is difficult to predict. Serological markers may help to identify suicide risk. We prospectively assessed 733 persons with a schizophrenia spectrum disorder, 483 with bipolar disorder, and 76 with major depressive disorder for an average of 8.15 years. The initial evaluation consisted of clinical and demographic data as well as a blood samples from which immunoglobulin G antibodies to herpes viruses and Toxoplasma gondii were measured. Suicide was determined using data from the National Death Index. Cox proportional hazard regression models examined the role of baseline variables on suicide outcomes. Suicide was associated with male sex, divorced/separated status, Caucasian race, and elevated levels of antibodies to Cytomegalovirus (CMV). Increasing levels of CMV antibodies were associated with increasing hazard ratios for suicide. The identification of serological variables associated with suicide might provide more personalized methods for suicide prevention. Abstract : Supplemental digital content is available in the text.